Inhibition of TLR8 mediated signaling promotes BCG induced apoptosis in THP-1 cells. (April 2016) - Tang, Jun; Zhan, Lingjun; Qin, Chuan
Abstract: Apoptosis was considered as one of the important host defense mechanisms against mycobacteria infection. In macrophage, the main target cell of Mycobacterium tuberculosis, apoptosis after infection could help kill the bacillus inside and process the antigens for further presentation and proper immune response. Here, we identified a role of TLR8 during the apoptosis induced by Bacillus Calmette Guérin (BCG) infection in THP-1 cells. Knockdown TLR8 further increased the apoptosis induced by BCG infection, and this enhanced apoptosis was caspase-dependent. During this process, Erk1/2, JNK and NFκB pathways were negatively affected and contributed to the enhanced apoptosis. Highlights: Inhibition of TLR8 aggravates cell death in BCG infected THP-1 cells. The increased apoptosis by TLR8 inhibition was Caspase-dependent. NFκB, Erk and JNK pathways were repressed on inhibition of TLR8.